Regeneration of Cochlear Synapses by Systemic Administration of a Bisphosphonate - Seist, Richard; Tong, Mingjie; Landegger, Lukas D.; Vasilijic, Sasa; Hyakusoku, Hiroshi; Katsumi, Sachiyo; McKenna, Charles E.; Edge, Albert S. B.; Stankovic, Konstantina M. (Frontiers in Molecular Neuroscience, 2020)
Sensorineural hearing loss (SNHL) caused by noise exposure and attendant loss of glutamatergic synapses between cochlear spiral ganglion neurons and hair cells is the most common sensory deficit worldwide. We show here that systemic administration of a bisphosphonate to mice 24 hours after synaptopathic noise exposure regenerated synapses between inner hair cells and spiral ganglion neurons, and restored cochlear function. We further demonstrate that this effect is mediated by inhibition of the mevalonate pathway. These results are highly significant because they suggest that bisphosphonates could reverse cochlear synaptopathy for the treatment of SNHL.